Comparative assessment of integrated phosphorus management practices on growth attributes, productivity and nutrient utilisation underpigeon pea (Cajanus cajan)–wheat (Tritium aestivum) system - DUTTA, ASIK; HAZRA, KALI KRISHNA; NATH, CHAITANYA P; KUMAR, NARENDRA; SINGH, RAGHAVENDRA; PRAHARAJ, C S; PATRA, ABHIK (The Indian Journal of Agricultural Sciences, 2025)
The present experiment was conducted during 2019–2022 at ICAR–Indian Institute of Pulses Research, Kanpur, Uttar Pradesh for assessing integrated phosphorus management strategies on growth attributes, yield and nutrient utilisation in pigeon pea [Cajanus cajan (L.) Millsp.]-wheat (Tritium aestivum L.) system. The experiment was laid out in a randomised block design (RBD) with four replication having treatments T1, Pi No-RDP (recommended dose of phosphorus) –WNo-RDP (only N and K); T2, Pi 100% RDP –W100% RDP; T3, Pi 60% of RDP + FYM (5 t/ha)- W60% of RDP; T4, Pi60% of RDP + PM (1 t/ha) -W60% of RDP; T5, Pi 60% of RDP + CR (50%) –W60% of RDP; T6, Pi60% of RDP + CR (50%) + PSB–W60% of RDP. Findings showed, nitrate reductase, chlorophyll-A and RGR impacted positively by integrated P-management practices in both the crops. Respective gain in yield under pigeon pea and wheat was 18% and 5% under T4 than T1 and on par with T2. Progressive release of nutrients along with improvement in soil physio-chemical condition have resulted higher P-uptake in T4 (26% and 11% in pigeon pea and wheat, respectively) than T1. Physiological efficiency impacted significantly under nutrient management strategies and showed much variability in wheat due to residual fertiliser impact and leaf fall of previous pigeon pea crop specifically in T1. In nutshell, application of 60% RDP in association with 1 t/ha poultry manure have proved a suitable alternative against conventional practice in pigeon pea-wheat system.